Hernia, Mesh, and Topical Antibiotics, Especially Gentamycin: Seeking the Evidence for the Perfect Outcome… - Kulacoglu, Hakan (Frontiers in Surgery, 2015)
Inguinal hernia repair is a clean surgical procedure and SSI rate is generally below 2%. Antibiotic prophylaxis is not routinely recommended, but it may be a good choice for institutions with high rates of wound infection (>5 %). Typical prophylaxis is the intravenous application of first or second generation cephalosporins before the skin incision. However, SSI rate remains more than 2% in many centers in spite of intravenous antibiotic prohylaxis. Even a 1% SSI rate may be unacceptable for the surgeons who specifically deal with hernia surgery. A hernia center targets to be a center of excellence not only in respect of recurrence rate but also for other postoperative outcomes, therefore a further measure is required for an excellent result regarding infection control. Topical gentamycin application in combination with preoperative single dose intravenous antibiotic may be a useful to obtain this perfect outcome. Data about this subject is not complete and high grade evidence has not been cumulated yet. Prospective randomized controlled trials can make our knowledge more solid about this subject and help the ssurgeons who seek perfect outcome regarding infection control in inguinal hernia surgery.